2022
DOI: 10.1002/jmv.27995
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of herpesvirus (HSV1, EBV, CMV, HHV6) seropositivity with depressive disorder and its clinical aspects: The first study in children

Abstract: Infections can lead to the onset of mood disorders in adults, partly through inflammatory mechanisms. However pediatric data are lacking. The aim of this study is to evaluate the relationship between depressive disorder and seropositivity of herpes virus infections in children.The sample group consisted of patients diagnosed with depressive disorder according to DSM-5 diagnostic criteria and healthy volunteers, being between 11 and 18 years with clinically normal mental capacity. All children completed DSM-5-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The adult prevalence of HHV in the general population is that HSV-1 infects about 70% of adults, HSV-2 about 30%, VZV more than 90%, EBV also more than 90%, CMV about 70%, and more than 95% of those 2 years and older are infected with either HHV-6A or HHV-6B or both ( 36 ). In contrast, in the depressed population, a study examining serologic testing in Turkish adolescents found HSV-1 in 71.4%, EBV in 82.9%, CMV in 94.2%, and HHV6 in 91.4%, and no statistically significant difference in healthy controls in the same study ( 35 ). No significant differences in HHV morbidity are expected between the general population and the depressed population, and it is likely that some infected individuals are more susceptible to depression than others.…”
Section: Mechanisms Of Disease For the Various Human Herpesviruses/th...mentioning
confidence: 90%
See 2 more Smart Citations
“…The adult prevalence of HHV in the general population is that HSV-1 infects about 70% of adults, HSV-2 about 30%, VZV more than 90%, EBV also more than 90%, CMV about 70%, and more than 95% of those 2 years and older are infected with either HHV-6A or HHV-6B or both ( 36 ). In contrast, in the depressed population, a study examining serologic testing in Turkish adolescents found HSV-1 in 71.4%, EBV in 82.9%, CMV in 94.2%, and HHV6 in 91.4%, and no statistically significant difference in healthy controls in the same study ( 35 ). No significant differences in HHV morbidity are expected between the general population and the depressed population, and it is likely that some infected individuals are more susceptible to depression than others.…”
Section: Mechanisms Of Disease For the Various Human Herpesviruses/th...mentioning
confidence: 90%
“…Cytomegalovirus infection is associated with decreased volume of gray matter in the brain in patients with MDD. This result suggests that cytomegalovirus infection may be a treatable cause of structural brain abnormalities in depressed patients (34). SITH-1-induced olfactory bulb apoptosis may also facilitate HHV-6B or other HHVs invasion into the brain, which is associated with worsening depressive symptoms (31).…”
Section: Hhv As a Risk For Worsening Mddmentioning
confidence: 99%
See 1 more Smart Citation
“…HHV-6B has been shown to be a risk factor for MDD. 30 , 31 , 32 so we thought it might be possible to obtain evidence for an association of depression and the microbiome by examining whether HHV-6B gene polymorphisms and MDD were related, and thereby solve the problem of missing heritability. Since SITH-1, a latent protein of HHV-6B, is a strong risk factor for MDD, 31 we attempted to identify polymorphisms of HHV-6B genes related to SITH-1.…”
Section: Introductionmentioning
confidence: 99%